Intraguild Predation or Spatial Separation? The efficacy and Interactions of Two Natural Enemy Species for the Biological Control of Pear Psyllid (Cacopsylla pyri) - Laura A. Reeves; Michelle T. Fountain; Michael P. D. Garratt; Deepa Senapathi (Journal of Insect Behavior, 2024)
Pear psyllid ( Cacopsylla pyri ) is a persistent pest to the pear industry; with an estimated cost of £5 million per annum in the UK alone. This phloem feeding insect is resistant to a large proportion of approved pesticides, necessitating the use of alternative control strategies. Many pear growers practice integrated pest management (IPM) of pear psyllid, focusing on maximizing natural enemy populations, whilst minimizing the use of agrochemical sprays. The anthocorid Anthocoris nemoralis and the European earwig Forficula auricularia are particularly effective at controlling pear psyllid populations during the summer months. Despite the effectiveness of both natural enemies, there is a lack of understanding on whether both species should be promoted together or separately, due to the risk of intraguild predation (IGP) or interference competition. Furthermore, abiotic factors including temperature may influence both behaviors, altering activity level and niche overlap. Although IGP and interference competition have been documented between multiple species of natural enemies neither have been studied between these two specific predators. Using microcosm experiments, olfactometer assays and survival analyses this study demonstrated whether A. nemoralis and F. auricularia can be used in synchrony to control pear psyllid. Results indicated that IGP is present; F. auricularia will consume A. nemoralis when predators are not spatially separate and in absence of psyllid prey. There was no evidence for interference competition, although both predators consumed more prey at higher temperatures. This confirms that pear growers can encourage both predators for the control of pear psyllid without losing predation efficacy.